2009
DOI: 10.1211/jpp.61.03.0011
|View full text |Cite
|
Sign up to set email alerts
|

1,8-Cineole induces relaxation in rat and guinea-pig airway smooth muscle

Abstract: 1,8-Cineole relaxed rat and guinea-pig (nonsensitized and ovalbumin-sensitized) airway smooth muscle by a nonspecific mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Contractions of tracheal smooth muscles by K + were also inhibited by 1,8-cineole [ 42 ] . These fi ndings were confi rmed on non-sensitized or ovalbumin-sensitized airway smooth muscle cells [ 43 ] .…”
Section: In Vitro Studiesmentioning
confidence: 67%
“…Contractions of tracheal smooth muscles by K + were also inhibited by 1,8-cineole [ 42 ] . These fi ndings were confi rmed on non-sensitized or ovalbumin-sensitized airway smooth muscle cells [ 43 ] .…”
Section: In Vitro Studiesmentioning
confidence: 67%
“…Eucalyptol‐containing products are widely used as a remedy for symptoms of the common cold and other respiratory infections and for alleviating pain (Juergens, ). In animal studies, eucalyptol was shown to counteract carrageenan‐induced oedema formation, acid‐, formalin‐ and heat‐evoked pain behaviour, gastric injury, colitis, allergen‐induced bronchoconstriction and inflammation, respiratory irritation due to inhalation of smoke irritants and endotoxin‐induced pulmonary inflammation and liver failure (Santos and Rao, , ; Santos et al, , ; Liapi et al, ; Bastos et al, ; Nascimento et al, ; Willis et al, ; Liu et al, ; Zhao et al, ; Ha et al, ; Rocha Caldas et al, ). Clinical studies administering eucalyptol observed anti‐inflammatory effects in asthmatics, alleviation of symptoms of rhino‐sinusitis and reduced chronic obstructive pulmonary disease (COPD) exacerbations (Juergens et al, ; Kehrl et al, ; Worth et al, ; Juergens, ).…”
Section: Introductionmentioning
confidence: 99%
“…The broadest field of application for 1,8-cineole is in the therapy of severe pulmonary diseases such as asthma, where the compound exhibits mucolytic, bronchodilating, and anti-inflammatory properties [6,7,8,9]. Similar effects play a role in the treatment of acute sinusitis, where 1,8-cineole is the pharmacologically active agent in some non-prescription pharmaceuticals [10,11].…”
Section: Introductionmentioning
confidence: 99%